2008
DOI: 10.2478/v10045-008-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Aphid Occurrence in Spring Barley in 1976-2007

Abstract: Abstract:Recently, considerable attention has been paid to climate change effects on nature and abundance of pests affecting agricultural crops. Our study was focused on the trends in aphid abundance during the growing seasons in spring barley in 1976-2007. Analysis was conducted based on the records of aphid abundance observations and detailed meteorological data.The first step in the study was to clarify the effects of temperature on aphid occurrence and abundance in spring barley. This part of the study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Similarly, Smatas et al (2008) reviewing the trends in aphid occurrence in spring barley from 1976 to 2007, found that the occurrence of aphids was more frequent due to increasing trend in air temperature during the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Smatas et al (2008) reviewing the trends in aphid occurrence in spring barley from 1976 to 2007, found that the occurrence of aphids was more frequent due to increasing trend in air temperature during the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…The payoff for a plant's investments in defenses can greatly increase with increasing herbivore loads, whereas both constitutive and inducible defenses reduce yields if expressed when herbivore pressure is low (Baldwin, ; Machado et al ., ). Herbivore occurrence and abundance vary enormously (up to 100%) by year even on small spatial scales (Smatas et al ., ), and attempting to decipher the effect of herbivore loads in meta‐analyses on Bt crops with cross‐year evaluations, on multiple fields, within or across countries, is technically challenging. Moreover, these meta‐analyses and their study components currently lack isogeneic controls, data on the levels of Cry protein throughout the season, and data on how protein levels correspond with herbivore loads and damage (Dandekar et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…R. padi is an important pest aphid species on cultivated cereals in Lithuania, its summer generations being subject of intense plant protection measures (Surkus 1997;Smatas 2006;Smatas et al 2008). R. nymphaeae, al-though listed as pest species of stone fruit production, has not been targeted for special plant protection measures yet (Rakauskas & Cichocka 2005).…”
Section: Introductionmentioning
confidence: 99%